2017
DOI: 10.1177/0954008317698547
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of graphene oxide concentration on properties and antifouling performance of PEES/GO ultrafiltration membranes

Abstract: In this study, asymmetric polyphenylene-ether-ether-sulfone (PEES) ultrafiltration (UF) membranes containing graphene oxide (GO) were prepared via non-solvent-induced phase separation process and N-methyl pyrrolidone was used as a solvent. The synthesis of GO was confirmed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analysis. The morphology of the prepared GO nanosheets was observed by field emission scanning electron microscope (FESEM) and transmission electron microscope. The memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The Ra measurements showed that the PCL surface showed average roughness of 21.2 ± 3.1 nm, and for PCL reinforced with GO, fGO, GO/TiO 2 , and fGO/TiO 2 , it was found to be 53.4 ± 4.1, 34.1 ± 1.2, 66.2 ± 5.2, and 43.3 ± 2.7 nm, respectively. Bala et al also reported similar results with the addition of GO nanosheets in the polyphenylene‐ether‐ether‐sulfone membranes and concluded that the roughness parameters also increased 48 . The films of PCL/fGO and PCL/fGO/TiO 2 displayed a relatively smooth surface morphology compared with pure PCL/GO and PCL/GO/TiO 2 films.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The Ra measurements showed that the PCL surface showed average roughness of 21.2 ± 3.1 nm, and for PCL reinforced with GO, fGO, GO/TiO 2 , and fGO/TiO 2 , it was found to be 53.4 ± 4.1, 34.1 ± 1.2, 66.2 ± 5.2, and 43.3 ± 2.7 nm, respectively. Bala et al also reported similar results with the addition of GO nanosheets in the polyphenylene‐ether‐ether‐sulfone membranes and concluded that the roughness parameters also increased 48 . The films of PCL/fGO and PCL/fGO/TiO 2 displayed a relatively smooth surface morphology compared with pure PCL/GO and PCL/GO/TiO 2 films.…”
Section: Resultsmentioning
confidence: 59%
“…Bala et al also reported similar results with the addition of GO nanosheets in the polyphenylene-ether-ether-sulfone membranes and concluded that the roughness parameters also increased. 48 The films of PCL/fGO and PCL/fGO/TiO 2 displayed a relatively smooth surface morphology compared with pure PCL/GO and PCL/GO/TiO 2 films. Although it was observed that Ra values increased with the addition of GO, Ra decreased with the addition of fGO and showed a good GO dispersion in the PCL matrix.…”
Section: Mass Loss (%)mentioning
confidence: 89%
“…Note also that the presence of hydroxyl groups of GO impacts the kinetic of mass transfers during membrane formation, hence affecting the membrane structure. More or larger macrovoids are likely to be observed if membranes are formed by wet-immersion, as pointed out by Bala et al [ 345 ] or Mohsenpour et al [ 304 ].…”
Section: Antifouling Materials For Polymeric Membranesmentioning
confidence: 97%
“…Carbon allotropes including graphene oxide (GO) and reduced graphene oxide (rGO), as well as other carbon materials such as multiwalled carbon nanotubes (MWCNTs) or carboxylated nanodiamonds (CNDs), have been used in the past decade to develop membranes by blending modification for water treatment [ 288 , 302 , 304 , 305 , 306 , 307 , 308 , 344 , 345 , 346 , 347 ].…”
Section: Antifouling Materials For Polymeric Membranesmentioning
confidence: 99%
“…Therefore, the development of a high-performance ceramic membrane material with a satisfactory protein antifouling performance is essential. In order to alleviate the membrane fouling, various approaches have been employed to modify the membrane surface charge [6], hydrophilicity-hydrophobicity performance [7], surface roughness [8,9], inhomogeneous pore size distribution [10], etc. Nanoparticles (NPs)-enhanced membranes with various functionalities have been proposed as high-performance antifouling membranes to separate and purify waste water [11,12].…”
Section: Introductionmentioning
confidence: 99%